What Effects From Peace in Reducing Poverty? A perspective from empirical records collected in the cities of Huambo and Luanda - Lopes, Carlos (2011)
Based on narratives made by Angolans living in the cities of Huambo and Luanda, the present article, anchored fundamentally on the assembled empirical records, searches for clues pointing to an answer (even if provisory) to the question posed in the title. Has peace in the Angolan context endorsed substantial progression in the reduction of poverty? This article explores, from the perspective of the interviewed individuals, several analytical axis: some consequences of the military conflict constituting impoverishment factors; benefits produced by war; self-attribution from the actors about their living conditions (how they position themselves in regard to their situation/condition of poverty and in relation to others) and respective expectations about the future. The article is the outcome of an investigation produced for the research project ‘Poverty and Peace in the PALOP, focused on the connections between poverty and war/peace in these countries and the manner this relation is perceived by the social actors.